Studi Pengaruh Penambahan Karbon Aktif Pada Optimasi Penurunan Warna Dan Kandungan Organik Pada Air Gambut Menggunakan Membran Ultrafiltasi - Rony Riduan (Universitas Lambung Mangkurat, 2005)
High organic content in peat water lower its quality as one of the surface water source. Ultra filtration membrane system is applicable to this problem with support from PAC (Powdered Activated Carbon) pre-treatment in order to enhance its organic removal performance.Effect of activated carbon pre-treatment to the performance of ultra filtration membrane system is analyzed from the optimum removal efficiency comparison. Optimation process is carried by analyzing the carbon active dose, contact time, acidity, applied pressure, and operating period effects in dead-end flow system. Statistical approach is used to support the optimation method with RSM (Response Surface Model) and regression analysis.Activated carbon pre-treatment enhanced the colour rejection by 9.37% and organic rejection by 2.3% compared to non-pre-treated. Flux difference from those methods is about 9.37% higher in the beginning of filtration process, and about 78% higher after 4 hours of operation. Carbon active pre-treatment effects flux significantly but not as great in colour and organic rejection. Optimum condition in organic removal from this system is measured at 3 bar applied pressure and ambient pH form carbon active pre-treatment. Total colour and organic rejection is 98.02% and 98.54%. The highest flux obtained from this method is 24.47 L/m2.hour. Generally, product from ultra filtration membrane system with activated carbon pre-treatment can achieve the drinking water quality standard.